Adoption of dairy farming technologies by small farm holders: practices and constraints - Quddus, MA (Bangladesh Journal of Animal Science, 2013)
In Bangladesh, usually, small scale farmers are not adopted to use all kinds of improved technologies in dairy farming. But, high level of technology adoption has a direct impact on milk yield and households income generation as well as dairy development. The objectives of this study was to determine the causes of adoption and non adoption of high yielding breed, the level of practices and constraints in adopting the improved technologies. The study was carried out in three different agro-ecological zones and 180 dairy cattle farmers were interviewed. Self practiced dairy technologies were listed, adoption score for each technology and adoption index for each farmer were studied. One-fourth farmers used artificial insemination for breeding purpose and two-fifth belonged to medium or high level of technology adoption. Only 35% farmers adopted crossbred cows and some others upgraded indigenous with exotic breeds. About 17.5% rural farmers and 70% semi-urban farmers reared crossbred cows and rural farmers are reluctant to utilize all kinds of improved technologies. Secondary and higher educated farmers were 9.7 times more likely to be adopting improved technologies compared to illiterate farmers. Top ranked constraints were ill equipped and negligible services at AI centre, no provision for testing of animals, poor knowledge of farmers about health care of animals and inadequate knowledge about proper feeding and balanced ration. Need more knowledge on improved technologies through training, availability of reliable and continuous technical assistance, availability and low price of concentrate feeds, increased and timely provision of medicine, increasing AI facilities, providing pure breed and strengthening extension services were the main suggestions from farmers. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14132 Bang. J. Anim. Sci. 2012. 41 (2): 124-135